Clinically simplified screening methods to evaluate maximum standard uptake value from F-18-FDG-PET/CT in patients with non-small-cell lung cancer. Issue 26 (June 2018) - Takeda, Yuichiro; Miura, Keita; Sato, Teruhiko; Tsujimoto, Yoshie; Nagano, Naoko; Nagasaka, Satoshi; Kina, Satsuki; Sugiyama, Haruhito
Abstract : Abstract: Maximum standard uptake value (SUVmax) of F-18-fluorodeoxyglucose positron emission tomography-computed tomography (FDG-PET/CT) is reportedly useful for evaluating regional lymph nodes (RLNs) of non-small-cell lung cancer (NSCLC) to predict malignancy. However, it is difficult for clinicians to measure SUVmax (mSUVmax) as calculated by a workstation. We assessed the utility of simplified SUVmax (sSUVmax) in screening RLNs for pathologic malignancy. The highest color was visually defined in the region of interest. The resulting color can be quantified using the color bar, and interpreted as sSUVmax. Patients in respiratory medicine and surgery who underwent both contrast-enhanced CT and FDG-PET/CT within 3 months before radical lobectomy were evaluated retrospectively. The correlation was examined by regression analysis and receiver operating characteristic (ROC) curve analyses. Participants comprised 69 patients with NSCLC treated between May 2009 and April 2016. Medical group comprised 22 patients from respiratory medicine. The prediction model could be written as a linear relationship (mSUVmax = 1.019 × sSUVmax; R 2  = 0.930). A total of 316 RLNs resected by surgery in total cohort were pathologically determined. From ROC curves, area under curve for sSUVmax was 0.72 (95% confidence interval, 0.61–0.83; P  < .0002). The cutoff sSUVmax was 2.42 (sensitivity, 52%; specificity, 88%; accuracy, 85%). The sSUVmax allows quantification of colors from FDG-PET/CT and shows a close correlation to mSUVmax. This value may have potential in screening for RLNs, and thoracic clinicians can readily determine the value. These findings may facilitate better planning of therapeutic strategy in the real world.